1974
DOI: 10.2135/cropsci1974.0011183x001400040008x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Row Spacing and Genotypic Frequency on the Yield of Soybean Blends1

Abstract: The effects of row spacing and genotypic frequency on the yield of soybean (Glycine max (L.) Merr.) blends were evaluated for use in establishing testing procedures for new blends. In 1969 and 1970, ‘Chippewa 64,’ ‘Hark,’ ‘Corsoy,’ ‘Provar,’ and ‘Amsoy’ were evaluated in all possible two‐component blends at the frequencies 3:1, 1:1, and 1:3, and in all possible three‐component blends in a 1:1:1 frequency. The blends and pure stands were tested for yield in 70‐ and 100‐cm rows.The average yield response of blen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…When yield data were pooled across densities, the greatest advantage of mixtures was obtained when Danas, the higher yielding component, contributed 75 % to those mixtures. Similar frequency dependent advantages were found in wheat (CHAPMAN et al 1969), soybeans (FEHR and RODRIGUEZ 1974), and maize (HOF.KSTRA et al 1985).…”
Section: Discussionsupporting
confidence: 54%
“…When yield data were pooled across densities, the greatest advantage of mixtures was obtained when Danas, the higher yielding component, contributed 75 % to those mixtures. Similar frequency dependent advantages were found in wheat (CHAPMAN et al 1969), soybeans (FEHR and RODRIGUEZ 1974), and maize (HOF.KSTRA et al 1985).…”
Section: Discussionsupporting
confidence: 54%
“…The agronomic reasons for the use of varietal mixture include stable yield, reduced lodging, diverse maturity groups for minimization of risk, and improved soil fertility utilization. Fehr and Rodriguez (1974), Shorter and Frey (1979), and Leon and Diepenbrock (1987) reported that mixtures yield better than the components. The gastronomic reasons were taste, baking quality, digestibility, and diversity of diet.…”
Section: Varietal Mixture (Polycultivar)mentioning
confidence: 99%
“…Modest yield advantages of up to 13% have been observed in mixed stands of soybean (Glycine mar (L.) Merr. ; Brim and Schutz, 1968;Fehr and Rodriguez, 1974), barley (Hordeurn uulgare L.; Clay and Allard, 1969), and oat (Aue m satiua L.; Frey and Maldonado, 1967;Shorter and Frey, 1979).…”
mentioning
confidence: 99%